The bullsh*t artist : lear to bluff, dupe, charm, and BS with the best of 'em - Kleinman, Paul (Avon, Mass. : Adams Media, 2011)
Provides an overview of various topics for just enough knowlege to control a conversation and remain confident.
Includes bibliographical referencesa and index.
Keywords: Conduct of life -- Humor; Conduct of life -- Humor